Effect of Glow-discharge Hydrogen Plasma Treatment on Zinc Oxide Layers Prepared through Pulsed Electrochemical Deposition and via SILAR Method - Klochko, N. P.; Klepikova, K. S.; Petrushenko, S. I.; Nikitin, A. V.; Kopach, V. R.; Khrypunova, I. V.; Zhadan, D. O.; Dukarov, S. V.; Lyubov, V. M.; Khrypunova, A. L. (Sumy State University, 2019)
In this work, we investigated the effect of glow-discharge H₂⁺ plasma treatment on ZnO layers deposited on fluorine doped tin oxide (FTO) glass substrates through low temperature aqueous solution growth, namely, via a pulsed electrochemical deposition and by successive ionic layer adsorption and reaction (SILAR) technique. It is shown that the crystal structure, surface morphology, chemical composition and optical properties obtain some destructive changes after plasma processing due to the creation of oxygen vacancies Vo and H-related defects, and additionally, because of the zinc oxide etching by the glow-discharge H₂⁺ plasma through reduction of zinc oxide and evaporation of Zn from the surface. Neverthe-less, our investigations show quite good stability of the ZnO layers to the plasma-induced radiation and chemical impacts under high total H₂⁺ fluence received by every ZnO/FTO sample ~ 8·10¹⁸ cm⁻².

У роботі ми досліджували вплив обробки в плазмі тліючого розряду Н₂⁺ на шари ZnO, які були нанесені на покриті плівками легованого фтором оксиду олова (FTO) скляні підкладки шляхом низько-температурного осадження з водних розчинів, а саме, методом імпульсного електрохімічного осадження і методом послідовної адсорбції і реакції іонних шарів (SILAR). Показано, що кристалічна структура, морфологія поверхні, хімічний склад і оптичні властивості після плазмової обробки зазнають деяких деструктивних змін через утворення кисневих вакансій Vo і пов'язаних з воднем дефектів, а також внаслідок того, що Н₂⁺-плазма тліючого розряду здатна травити ZnO шляхом відновлення оксиду цинку і випаровування з поверхні Zn. Проте в цілому, наші дослідження продемонстрували досить добру стійкість шарів ZnO до радіаційного та хімічного впливів плазми при одержаній кожним зразком ZnO/FTO високій сумарній густині потоку Н₂⁺ приблизно 8·10¹⁸ см⁻².
Вплив обробки у водневій плазмі тліючого розряду на шари оксиду цинку, виготовлені імпульсним електрохімічним осадженням і методом SILAR
Keywords: glow discharge; zinc oxide; pulse electrodeposition; SILAR; hydrogen plasma treatment; хімічні реакції; воднева плазмова обробка; випаровування; кристалічна структура; імпульси